Cross-cultural Adaptation and Validation of Beliefs about Medicines Questionnaire on Asthma and Chronic Obstructive Pulmonary Disease Patients - (:unkn) unknown (BILIMSEL TIP PUBLISHING HOUSE, 2018)
OBJECTIVES: Inadequate adaptation to long-term treatment of chronic illnesses is the most common reason for the inability to obtain the benefits medications can provide. Treatment compliance is influenced by several factors. Beliefs about Medicines Questionnaire (BMQ) developed by Horne et al. in 1999 to evaluate the cognitive representation of medicines have many validation studies, which resulted in good psychometric properties. The aim of the present study was to evaluate the reliability and validity of the BMQ Turkish translation in patients with asthma and chronic obstructive pulmonary disease (COPD). MATERIAL AND METHODS: Fifty asthma and 50 COPD patients participated in this methodological study. The scale was adapted to Turkish through translation, comparison with other language versions, back translation, and a pre-test. The structural validity was assessed using factor analysis. RESULTS: Similar to the original scale, factor analysis confirmed that BMQ had a four-factor structure that accounts for 58.23% of the total variance. The BMQ showed an acceptable internal consistency (Cronbach's alpha coefficient: specific-necessity, 0.832: specific-concerns, 0.722; general-harm, 0.792; and general-overuse, 0.682). The factor analysis revealed the same patterns for all questions between the Turkish and original scales. CONCLUSION: The psychometric properties of the BMQ were consistent with those reported in the original study. We found that the Turkish translation of BMQ is a valid and reliable tool for assessing medicine-related beliefs in patients with asthma and COPD.
Keywords: Attitudes; beliefs; medication adherence; validation; ADHERENCE; PERSISTENCE; CHILDREN